Goldenberry (Physalis peruviana) alleviates hepatic oxidative stress and metabolic syndrome in obese rats - Sherif A. Abdelmottaleb Moussa, Fatma A. A. Ibrahim, Marawan Abd Elbaset, Samir W. Aziz, Fatma A. Morsy, Noha Abdellatif, Atef Attia, Sayed A. El Toumy, Josline Y. Salib, Samir A. E. Bashandy (Journal of Applied Pharmaceutical Science, 2022)
The objective of this study was to investigate the effect of goldenberry (GB) (Physalis peruviana) extract supplementation on fat accumulation, hepatic oxidative damage, hepatic fat deposition, inflammation, and hepatic scarring, as well as metabolic syndrome in obese rats. Obesity was induced by feeding rats a high-fat diet for 12 weeks. Female Wister rats were divided into four groups (eight each): control group, obese group, obese + a low-dose GB (200 mg/kg), and obese + a high-dose GB (400 mg/kg). Body mass index (BMI), adipose tissue hormones, lipid profile, liver enzymes, hepatic oxidative stress parameters, and hepatic histopathological changes were assessed. Treating obese rats with GB supplementation reduced their increased body weight, BMI, leptin level, cholesterol, triglycerides, glucose, and insulin resistance index (homeostatic model assessment for insulin resistance). Moreover, the GB regime significantly improved the antioxidant parameters in the liver. In addition, it has shown a significant antiobesity impact by lessening body weight, oxidative damage, BMI, lipids, and insulin insensitivity. Eventually, administration of GB extracts reduced markers of inflammation [tumor necrosis factor-alpha, interleukin (IL)-2, IL-6, and C-reactive protein], fat deposition, steatosis, and fibrosis in the liver of the obese rats. Moreover, GB intake can be used in coupling with a healthy diet to assist obese rats suffering from metabolic syndrome.
Keywords: Obesity, goldenberry, inflammation markers, oxidative stress, metabolic syndrome, liver pathology